856 Preliminary review of Diabetes Mellitus incidence in patients treated with immune checkpoint inhibitors (ICI) therapy – Roswell Park Comprehensive Cancer Center (RPCCC) experience. (9th November 2020) - Zhang, Zhen; Riebandt, Grazyna; Sharma, Rajeev; Hamad, Lamya; Scott, Jordan; Plewinski, Laurie
Abstract : Background: Immune checkpoint inhibitor (ICI) therapy has revolutionized cancer treatment and has become a standard of care. There are now numerous FDA approved indications for ICIs and an increasing number of patients receiving these treatments, which has led to an increase in the risk of immune-related adverse events (irAEs) including endocrinopathies. Diabetes mellitus is a rare irAE of ICI therapy with an approximate incidence of 1-2%. There is paucity of data in literature about incidence, characteristics and possible predictive factors of ICI-induced diabetes mellitus. Due to limited data on ICI-induced diabetes, we conducted a retrospective review of patients who received ICI therapy at RPCCC and developed diabetes mellitus. The goal of this study is to report incidence and characteristics of new onset and worsening of diabetes in patients treated with ICI therapy. Methods: We conducted a retrospective chart review of patients who received ICIs treatment from January 1st, 2010 to May 15th, 2020. We identified patients with newly diagnosed diabetes and worsening of preexisting diabetes. Newly diagnosed diabetes was defined as fasting blood glucose ≥ 126 or hemoglobin A1c (HbA1c) ≥ 6.5, random blood glucose ≥ 200 mg/dL with symptoms or 2-hour blood glucose ≥ 200 mg/dL on oral glucose tolerance test. Worsening of preexisting diabetes, defined as more than 0.5% increase in absolute HbA1c value in preceding 3-6 months or need for insulin in stable patients with diabetes on oral hypoglycemic agents. Subjects with pre-existing type 1 diabetes mellitus or on systemic corticosteroids for more than 1-week duration prior to diagnosis of diabetes mellitus were excluded. Results: Among 2, 382 reviewed patients who received one or multiple ICIs, 15 patients developed new onset of diabetes and 12 patients experienced worsening of pre-existing Type 2 diabetes. In these 27 patients, 8 presented with diabetic ketoacidosis. Median time to new onset diabetes or worsening diabetes from ICI treatment initiation was 19 weeks, ranging from 2 to 320 weeks. Positive autoantibodies were found in 3 patients, among who 2 patients with positive Glutamic Acid Decarboxylase (GAD65) antibodies and one patient with positive insulin autoantibodies (IAA). Conclusions: The incidence of new onset diabetes and worsening diabetes in patients treated with ICI therapy was 1.1%. Ethics Approval: The study was approved by Roswell Park Comprehensive Cancer Center's Ethics Board, IRB ID STUDY00001278/BDR 129520. Consent exempt: References: Azoury SC, Straughan DM, Shukla V. Immune checkpoint inhibitors for cancer therapy: clinical efficacy and safety. Curr Cancer Drug Targets 2015;15(6):452-462. Puzanov I, Diab A, Abdallah K, et al. Managing toxicities associated with immune checkpoint inhibitors: consensus recommendations from the society for immunotherapy of cancer (SITC) toxicity management working group. J Immunother Cancer 2017;5(1):95. Akturk HK, Kahramangil D, Sarwal A, Hoffecker L, Murad MH, Michels AW. Immune checkpoint inhibitor-induced type 1 diabetes: a systematic review and meta-analysis. Diabet Med 2019;36(9):1075-1081.